Proximal femoral nail antirotation versus InterTan nail for the treatment of intertrochanteric fractures: A systematic review and meta-analysis - Liao, Chang-sheng; He, Fang-zheng; Li, Xi-yong; Han, Peng-fei (PloS one, 2024)
This meta-analysis compared the efficacy and safety of Proximal Femoral Nail Antirotation (PFNA) and InterTan Nail in the treatment of intertrochanteric fractures. Given the high incidence of femoral intertrochanteric fractures in the elderly population and its impact on quality of life, choosing the most effective and safest surgical option is crucial. PFNA and InterTan are currently two commonly used techniques, but there is a lack of systematic evaluation comparing their safety and effectiveness. This study aims to fill this knowledge gap through Meta-analysis, providing clinicians with evidence-based treatment recommendations. A computer search was used to search for published literature on PFNA and InterTan in the treatment of intertrochanteric fractures in PubMed (Medline), Web of Science, Embase, Cochrane Library (CENTRAL), Cinahl, CBM, and CNKI.A total of 853 related literatures were retrieved, and 15 literatures were finally included. Newcastle-Ottawa-Scale and Cochrane systematic review methodologies were used to assess the quality of the literature. Meta-analysis was performed using Review Manager 5.4 software, following data extraction. The comparison found that during the surgical treatment of intertrochanteric fractures, the operation time, fluoroscopy time, and blood loss in the PFNA group were significantly shorter than those in the InterTan group, and the difference was statistically significant. In terms of postoperative complication rates, the InterTan group had a significant advantage over the PFNA group. Shaft fracture, varus collapse, cut out, screw migration, and pain of hip and thigh were the most likely to occur in the PFNA group, and the differences were all statistically significant. In terms of postoperative efficacy, the results of the PFNA group and the InterTan group were comparable, and there was no significant differences. When selecting surgical techniques for the treatment of femoral intertrochanteric fractures, it is necessary to conduct individualized assessments based on the patient's overall health status, surgical tolerance, and post-operative recovery needs. For patients who cannot tolerate long-term surgery or are in poor physical condition, PFNA may be more appropriate. While for patients who can tolerate long-term surgery or have more complex conditions, InterTan may be more suitable.